Composition and hygroscopicity of the Los Angeles Aerosol: CalNex. Issue 7 (11th April 2013) - Hersey, Scott P.; Craven, Jill S.; Metcalf, Andrew R.; Lin, Jack; Lathem, Terry; Suski, Kaitlyn J.; Cahill, John F.; Duong, Hanh T.; Sorooshian, Armin; Jonsson, Haflidi H.; Shiraiwa, Manabu; Zuend, Andreas; et al.
Abstract: [1] Aircraft‐based measurements of aerosol composition, either bulk or single‐particle, and both subsaturated and supersaturated hygroscopicity were made in the Los Angeles Basin and its outflows during May 2010 during the CalNex field study. Aerosol composition evolves from source‐rich areas in the western Basin to downwind sites in the eastern Basin, evidenced by transition from an external to internal mixture, as well as enhancements in organic O : C ratio, the amount of organics and nitrate internally mixed on almost all particle types, and coating thickness on refractory black carbon (rBC). Transport into hot, dilute outflow regions leads to significant volatilization of semivolatile material, resulting in a unimodal aerosol comprising primarily oxygenated, low‐volatility, water‐soluble organics and sulfate. The fraction of particles with rBC or soot cores is between 27 and 51% based on data from a Single Particle Soot Photometer (SP2) and Aerosol Time of Flight Mass Spectrometer (ATOFMS). Secondary organics appear to inhibit subsaturated water uptake in aged particles, while CCN activity is enhanced with photochemical age. A biomass‐burning event resulted in suppression of subsaturated hygroscopicity but enhancement in CCN activity, suggesting that BB particles may be nonhygroscopic at subsaturated RH but are important sources of CCN. Aerosol aging and biomass burning can lead to discrepancies between subsaturated and supersaturated hygroscopicity that may be related to mixing state. In the cases of biomass burning aerosol and aged particles coated with secondary material, more than a single parameter representation of subsaturated hygroscopicity and CCN activity is needed. Key Points: Aged aerosol is internally mixed; organics and nitrate coat all particle types Aged particles exhibit suppressed subsaturated k but enhanced CCN activity Organic coatings inhibit subsaturated water uptake but not CCN activity